Policy Framing Analysis Of The Ministry Of Tourism Of The Republic Of Indonesia Related To The Covid-19 Pandemic On The Kompas.Com National News Portal Website - Shandy, Shandy; Gilang, Wayan Gede; Nugroho, Saptono (Rumah Jurnal UNEJ, 2022)
This study aims to find out how the framing of the Kompas.com news portal regarding the Indonesian Ministry of Tourism's Policy Regarding the Covid-19 Pandemic. This policy was formed so that the community and tourism workers still maintain the health and safety of every individual in the community. There is a need for news framing (Framing) in kompas.com online media. Especially in the policy of the tourism ministry to deal with the Covid-19 pandemic, and how the impacts or complaints that occur in the community and expectations of the government. Assumptions, there are aspects that are highlighted that tend to be forced and put aside, this can be answered by framing analysis. This research on the framing of the policy news of the Ministry of Tourism and Creative Economy on the impact of the Covid-19 pandemic uses a qualitative approach with the framing analysis method, the type of descriptive qualitative research. Suggestions that can be given by researchers are suggestions for the government, the online media kompas.com, and also the public in making decisions, policies in gathering news, and in responding to and understanding decisions made by the government.